Relationship between last mile and milk run: literature review and classification of solutions to the main challenges facing Peru in last mile logistics - Ramos Quispe, Julio Abraham (2022)
Given the logistic scenarios faced by Peru, this article analyzes the relationship between Milk Run and Last Mile through a literature review; in this sense, it presents a general classification of Last Mile components and offers solution alter[1]natives to its challenges. Thus, it provides a better perspective of the algorithms regarding improvement, distribution, and optimization.